Highly sensitive graphene-based ammonia sensor enhanced by electrophoretic deposition of MXene. (15th January 2023) - Li, Quanfu; Xu, Minhua; Jiang, Chunsheng; Song, Shuxiang; Li, Tinghui; Sun, Manli; Chen, Wuliang; Peng, Huiling
Abstract: Herein, we reported a gas sensor based on MXene/Graphene composite sensitive film for low-concentration ammonia detection. Specifically, we use the electrophoretic deposition method to uniformly deposit MXene on the graphene film surface of the graphene sensor, thereby constructing the MXene/Graphene composite sensitive film. The ammonia sensitivity test results show that the MXene/Graphene composite film sensor exhibits fast response, high sensitivity and excellent selectivity to ammonia at room temperature and high humidity. At the same test concentration (100 ppm), the sensitivity of the MXene/Graphene sensor is 3 times higher than that of the graphene sensor, 2 times higher than that of the MXene film sensor, reaching 25%, and its theoretical limit of detection is 56 ppb. The response time is only 26 s and the recovery time is 148 s, while the response time of the graphene sensor is 228 s. The MXene/Graphene sensitive film takes full advantage of the hydrophilicity and abundant surface functional groups of MXene, and the excellent electrical conductivity of graphene, which solves the problems of low sensitivity, slow response speed, and inability to completely desorb ammonia gas of pure MXene or graphene. Potential applications in designing next-generation portable gas sensors for human breath detection analysis. Graphical abstract: Image 1